Modelling the optical properties of Benzochalcogenodiazole-based Copolymers using Tuned Range-Separated Hybrid Functionals - Ruiz-Delgado, María del Carmen; Gámez Valenzuela, Sergio; Badía-Domínguez, María Irene; Herrero-Carvajal, Daniel; Seferos, D. S.; Gibson, G. L.; López-Navarrete, Juan Teodomiro (My University, 2019)
Since the discovery of organic semiconductors, these systems have been deeply investigated and many strategies to module their optical and electronic properties have been established. In this sense, Donor-acceptor (D−A) approach to conjugated polymer design has become a widely used method for preparing conjugated polymers with narrow band gaps. This approach involves synthesizing a polymer with a delocalized π-electron system that comprises alternating electron-rich (donor) and electron-deficient (acceptor) repeat units. The combination of high-lying HOMO levels (residing on the donor units) and low-lying LUMO levels (residing on the acceptor units) results in an overall narrow band gap for the polymer. In this sense, poly(cyclopentadithiophene)benzothiadiazole is a D−A polymer for which power conversion efficiencies in solar cells of 5 6 % are reported. In this work, we use density functional theory (DFT) calculations to investigate the tuning of the electronic and structural properties of cyclopentadithiophene ben zochalcogenodiazole D−A polymers, wherein a single atom in the benzochalcogenodiazole unit is varied from sulfur to selenium to tellurium. Resonance Raman (RR) spectroscopy is also used to describe the nature of the electronic excitations. Improved prediction of the optical properties h as been obtained by using long range corrected functionals functionals, considering both tuned and default range separation parameters, aiming at predicting their optical and charge transport properties.
Keywords: Semiconductores orgánicos; Polímeros; Quantum chemical calculations; Benzocharcogenodiazole; Polymers; Optical Properties